2018
DOI: 10.1002/jcb.27713
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatic treatment effect of triple negative breast cancer cell line with copper (I)‐nicotinate complex

Abstract: The treatment of triple-negative breast cancer (TNBC) remains a major challenge. The present study aimed to throw more light on the role of copper (I)-nicotinate complex (CNC) as an antitumor as well as a proapoptotic agent. In this study, the HCC-1806 cell line was used as a model for TNBC. Cell cycle, apoptosis assay, and programmed cell death protein-1 were investigated by flowcytometry. Besides, the comet assay was performed using a fluorescence microscope. The enzyme-linked immunosorbent assay technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Recently, Different molecular studies have allowed for the emergence of targeted therapies 48 , whereas others have evolved to explain mechanisms of resistance [49][50][51][52][53] . Several signalling pathways and biomarkers have been shown to be implicated in TNBC progression such as BAX/BCL2, HSP90α, EGFR, VEGF, survivin, CDK1, caspases, mTOR, and Ras/Raf/MEK/ERK 22,[52][53][54][55][56][57][58][59][60] . MDA-MB-231 cells are the typical cell line used in cancer research as a tool to explore the mechanisms of numerous diseases, and identify new therapeutic targets 61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Different molecular studies have allowed for the emergence of targeted therapies 48 , whereas others have evolved to explain mechanisms of resistance [49][50][51][52][53] . Several signalling pathways and biomarkers have been shown to be implicated in TNBC progression such as BAX/BCL2, HSP90α, EGFR, VEGF, survivin, CDK1, caspases, mTOR, and Ras/Raf/MEK/ERK 22,[52][53][54][55][56][57][58][59][60] . MDA-MB-231 cells are the typical cell line used in cancer research as a tool to explore the mechanisms of numerous diseases, and identify new therapeutic targets 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 3 (and its cleavage CC3) is the central member of the caspase family, which is cleaved into 29-and 85-kDa fragments by PARP-1 during the early stages of apoptosis, mediating tumour repopulation in apoptotic tumour cells 103 . Recent studies have revealed the close association of caspase 3 expression and breast cancer where a disease with lower or absent apoptosis index has a bad prognosis 55,103 . The caspase 3/9 activation was associated with inhibited cell proliferation, induced apoptosis, as well as increased BAX protein expression in prostate cancer 31,104 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐time was performed using the BeyoRT™ II First Strand cDNA Synthesis Kit (Beyotime Institute of Biotechnology) and then qPCR was performed using the Light‑Cycler 480 System (Roche Diagnostics), with SYBR Green reagent (Takara Biotechnology, Co., Ltd.). The amplification reactions were according to the following thermal cycling conditions: 95℃ for 10 min, 40 cycles of 95˚C for 15 s, and 60˚C for 30 s. The quantification was expressed as the ratio of target genes to GAPDH mRNA using the 2 −ΔΔCq method (Abdel‐Mohsen et al., 2017; Abdel‐Mohsen et al, 2019a, 2019b). reverse transcription‑quantitative polymerase chain reaction (RT‑qPCR) was accomplished by the following primers:…”
Section: Methodsmentioning
confidence: 99%
“…Excessive apoptosis in tubular epithelial cells results in tubular atrophy and loss of functional mass (El‐Shafey & Elsherbiny, 2020). CsA induces apoptosis through activation of caspase‐9, caspase‐3, and Fas‐tumor necrosis factor receptor 1‐mediated pathway, leading to the loss of mitochondrial transmembrane potential and apoptotic cell death (Abdel‐Mohsen, Toson, et al., 2019). Co‐administration of SL and FS attenuated the increase of apoptotic cells, suggesting their antiapoptotic role.…”
Section: Discussionmentioning
confidence: 99%